Wellbeing and Work Design in Brazilian Teleworkers - Mishima-Santos, Viviane; Sticca, Marina Greghi; Pérez-Nebra, Amalia R. (Frontiers in Psychology, 2021)
Studies suggest that job characteristics may be related to workers’ wellbeing. However, little is known about how these work characteristics may influence wellbeing in telework in the face of the long period of social isolation and restrictions imposed by COVID-19. This study aimed to relate work characteristics in remote work to wellbeing using a two-stage multi-method approach. The general hypothesis is that different work characteristics will be organized into different groups and related to wellbeing. In Step 1, a total of 108 teleworkers who participated in compulsory telework conditions, answered the Work Design Questionnaire. A cluster analysis was conducted in which two clusters emerged based solely on their valence. The variables that contributed most to the cluster were feedback from job, social support, problem-solving, and decision and execution autonomy. Cluster 1 aggregated higher scores on work characteristics, and Cluster 2, lower scores. In Step two, 27 of these workers were blinded interviewed. The corpus was analyzed using the Iramuteq software. Five classes of words emerged from the interviews: Class 1 (wellbeing), Class 2, (work dissatisfaction lexicon), Class 3 (role clarity), Class 4 (work demands), and Class 5 (work resources, including receiving feedback, conversations, praise, and support). Chi-square analysis suggests significant differences in classes 2, 3, 4, and 5. Cluster 1 appears more frequently in Class 3 and less frequently in 2 and 4. Cluster 2 is more frequent in classes 2 and 4 and less frequent in Class 5. Class 1 shows no significant difference. These results partially support the general hypothesis that work characteristics are related to the wellbeing of teleworkers, but in the sense that it prevents suffering but not necessarily promotes wellbeing. The results contribute to the understanding of the relationship between work characteristics and wellbeing during the pandemic by using a different methodological approach, describing which characteristics are the most significant in differentiating the perception of the groups.